THE EFFECT OF AROMATHERAPY WITH ORANGE ESSENTIAL OIL ON ANXIETY AND PAIN IN PATIENTS WITH FRACTURED LIMBS ADMITTED TO AN EMERGENCY WARD: A RANDOMIZED CLINICAL TRIAL - Davood Hekmatpou; Yasaman Pourandish; Pouran Varvani Farahani; Ramin Parvizrad (University of Ostrava, 2017)
Aim: Pain and anxiety are unpleasant feelings associated with actual or potential tissue damage. The goal of this study is to determine the effect of aromatherapy with orange oil on the pain and anxiety of patients with limb fractures hospitalized in an emergency ward. Design: Randomized Clinical Trial. Methods: 60 patients in an emergency ward were allocated to one of two groups: an experimental and a control group, using a randomized blocking sampling method. Four drops of orange oil were poured onto a pad, which was attached to his/her collar by a plastic safety pin (posing no risk to patients), so that the distance from the patient's head was not more than 20 cm. To prevent loss of aroma from the impregnated pad, the fragrance was replaced every hour. Pain was measured every hour for six hours, and the patients' anxiety rate was measured before and after the intervention. All data were analysed using SPSS 21. Results: Mean age of participants was 37.93 ± 18.19 years. Most fractures were in the scapula area (11 patients - 18.3%). The results indicated a significant difference between the mean of anxiety in the intervention group (p < 0.001) compared to the control group (p = 0.339). Regarding pain, a Friedman test showed significant differences between the mean of pain in the intervention group (p < 0.001) compared to the control group (p = 0.339). Conclusion: Aromatherapy with orange essential oil reduced pain and anxiety in patients with limb fractures. Therefore, the application of aromatherapy with orange essential oil as a complementary therapy is recommended for these patients. Keywords: aromatherapy, anxiety, limb fracture, orange oil, pain, relief.